11C-Metomidate PET-CT versus adrenal vein sampling to subtype primary aldosteronism: a prospective clinical trial. Issue 6 (June 2022) - Puar, Troy H.; Khoo, Chin Meng; Tan, Colin Jingxian; Tong, Aaron Kian Ti; Tan, Michael Chien Sheng; Teo, Ada Ee Der; Ng, Keng Sin; Wong, Kang Min; Reilhac, Anthonin; O'Doherty, Jim; Gomez-Sanchez, Celso E.; Kek, Peng Chin; et al.
Abstract : Objective: Adrenal vein sampling (AVS) is recommended to subtype primary aldosteronism, but it is technically challenging. We compared 11 C-Metomidate-PET-computed tomography (PET-CT) and AVS for subtyping of primary aldosteronism. Methods: Patients with confirmed primary aldosteronism underwent both AVS and 11 C-Metomidate PET-CT (post-dexamethasone). All results were reviewed at a multidisciplinary meeting to decide on final subtype diagnosis. Primary outcome was accuracy of PET versus AVS to diagnosis of unilateral primary aldosteronism based on post-surgical biochemical cure. Secondary outcome was accuracy of both tests to final subtype diagnosis. Results: All 25 patients recruited underwent PET and successful AVS (100%). Final diagnosis was unilateral in 22 patients, bilateral in two and indeterminate in one due to discordant lateralization. Twenty patients with unilateral primary aldosteronism underwent surgery, with 100% complete biochemical success, and 75% complete/partial clinical success. For the primary outcome, sensitivity of PET was 80% [95% confidence interval (95% CI): 56.3–94.3] and AVS was 75% (95% CI: 50.9–91.3). For the secondary outcome, sensitivity and specificity of PET was 81.9% (95% CI: 59.7–94.8) and 100% (95% CI: 15.8–100), and AVS was 68.2% (95% CI: 45.1–86.1) and 100% (95% CI: 15.8–100), respectively. Twelve out of 20 (60%) patients had both PET and AVS lateralization, four (20%) PET-only, three (15%) AVS-only, while one patient did not lateralize on PET or AVS. Post-surgery outcomes did not differ between patients identified by either test. Conclusion: In our pilot study, 11 C-Metomidate PET-CT performed comparably to AVS, and this should be validated in larger studies. PET identified patients with unilateral primary aldosteronism missed on AVS, and these tests could be used together to identify more patients with unilateral primary aldosteronism. Video Abstract: http://links.lww.com/HJH/B918 .